Arte, cultura e saúde mental: histórias de adolescentes vinculados a projetos artístico-culturais - Souza, Thaís Thaler (Universidade Federal de São Carlos, 2022)
Introduction: The mental health of adolescents is an emerging research theme that often reflects an adult-centered perspective and realities that may not be fully compatible with the context of the Global South. This highlights the need to capture the voices of this population while emphasizing the importance of mental health promotion within the perspective of psychosocial care and local contexts. Art and culture play a crucial role in mental health and psychosocial care, particularly within its sociocultural dimension. Therefore, studies that investigate the relationship between art, culture and mental health among adolescents are vital to creating new life opportunities and enhancing the quality of care. Objectives: The main objective of this study was to examine adolescents' perceptions of their experiences with art and culture projects and how it relates to their own mental health. As specific objectives, this study aimed to (1) investigate how adolescents evaluate access to art and culture activities in their local communities; (2) understand how art and culture activities influence the life stories of adolescents; (3) identify how adolescents have engaged in art and culture activities during the COVID-19 pandemic; and (4) produce and disseminate a documentary about the participants' experience in art and culture projects, in collaboration with them, using a participatory method. Methodology: This study involved six adolescents from vulnerable contexts who participated in art and culture projects. The participatory research methodthis used two strategies for the construction of data. The first consisted of the development of oral historys of life and the second concerned the organization of discussion groups on the topic of art, culture and mental health. Using Bardin's thematic content analysis technique, narratives derived from the oral histories were analyzed. The axes and categories identified by the researcher were validated by the discussion group participants. As part of the discussion groups, the proposed topics were explored further with participants to collaboratively produce a documentary, which was the main outcome of the study and a contribution to society. Results: Participants in the study were involved in a variety of art and culture activities, including capoeira, writing, clay sculpture, drawing and music. In view of the adolescent's narratives, four thematic axes were identified. Axis One was the 'bond and knots: the family's role in the development of support networks'; Axis Two was 'Transgression and other forms of freedom and well-being'; Axis Three was 'You are not alone, see?'; Axis Four was 'COVID-19 kit: resilience and tenderness. Within these themes, the axes were further explored into 11 categories. Discussion: Results indicate that the research participants placed a high level of importance and idealization on their family members, particularly their mothers. The mother is an important reference, which raises the reflection on the relationship between gender and family care. Additionally, they indicated that fraternal relationships within cultural and artistic spaces are organized by a perspective of social roles within the family that sometimes prevent or facilitate access to projects. While families reported reaping limited benefits from the projects' political and emancipatory potential, the participants noted profound subjective changes as a result of their participation. Participants also reported an increased sense of critical skills, social contractuality, belonging, urban mobility and the emancipatory political potential with the participation. According to them, the coordinators of art and culture projects were a source of support, a point of reference and a means of obtaining access to new opportunities essential for their continued involvement in the projects. The pandemic was also frequently mentioned by participants, who recognized difficulties and social problems associated with it, such as dropping out of school. In spite of this, they also identified the pandemic as a positive period and a time of personal growth and development. It is identified that art-culture projects are structured in a network developed by affection and as a support point chosen by the adolescents. The entire research process culminated in the creation of a documentary entitled "Young art: creators of their own opportunities", which was credited by the teenagers as an opportunity to be represented and to participate in something new. Final considerations: according to the participants, arts and culture projects provided them with spaces for participation, cultural expression, citizenship reclamation, enhanced critical skills, increased access to new opportunities, greater agency repertoire and a fight for quality of life, all of which influence the proposal for psychosocial care and mental health promotion.
Art, culture and mental health: stories of adolescents linked to artistic-cultural projects
Keywords: Promoção em saúde mental; Atenção psicossocial; Adolescentes; Arte-cultura; Terapia Ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL